Towards Efficient Integrated Perovskite/Organic Bulk Heterojunction Solar Cells: Interfacial Energetic Requirement to Reduce Charge Carrier Recombination Losses. (29th April 2020) - Daboczi, Matyas; Kim, Jinhyun; Lee, Jinho; Kang, Hongkyu; Hamilton, Iain; Lin, Chieh‐Ting; Dimitrov, Stoichko D.; McLachlan, Martyn A.; Lee, Kwanghee; Durrant, James R.; Kim, Ji‐Seon
Abstract: Integrated perovskite/organic bulk heterojunction (BHJ) solar cells have the potential to enhance the efficiency of perovskite solar cells by a simple one‐step deposition of an organic BHJ blend photoactive layer on top of the perovskite absorber. It is found that inverted structure integrated solar cells show significantly increased short‐circuit current ( J sc ) gained from the complementary absorption of the organic BHJ layer compared to the reference perovskite‐only devices. However, this increase in J sc is not directly reflected as an increase in power conversion efficiency of the devices due to a loss of fill factor. Herein, the origin of this efficiency loss is investigated. It is found that a significant energetic barrier (≈250 meV) exists at the perovskite/organic BHJ interface. This interfacial barrier prevents efficient transport of photogenerated charge carriers (holes) from the BHJ layer to the perovskite layer, leading to charge accumulation at the perovskite/BHJ interface. Such accumulation is found to cause undesirable recombination of charge carriers, lowering surface photovoltage of the photoactive layers and device efficiency via fill factor loss. The results highlight a critical role of the interfacial energetics in such integrated cells and provide useful guidelines for photoactive materials (both perovskite and organic semiconductors) required for high‐performance devices. Abstract : A 250 meV energetic barrier is found to lead to detrimental interfacial charge carrier recombination at the interfaces of the two photoactive layers in a perovskite/organic bulk heterojunction solar cell. Based on the energetic requirement identified, new device design strategies are suggested to eliminate losses in integrated perovskite solar cells and hence to achieve higher efficiencies than those observed in perovskite‐only devices.